Targeting Mitochondrial Oxidative Phosphorylation Abrogated Irinotecan Resistance in NSCLC. Issue 1 (December 2018) - Lee, Soohyun; Lee, Jae-Seon; Seo, Jinho; Lee, Seon-Hyeong; Kang, Joon; Song, Jaewhan; Kim, Soo-Youl
Abstract Anticancer drug resistance is a major challenge of cancer therapy. We found that irinotecan-resistant NSCLC cells showed increased mitochondrial oxidative phosphorylation compared to the drug sensitive NSCLC cells. Previously, we found that combined inhibition of aldehyde dehydrogenase using gossypol, and mitochondrial complex I using phenformin, effectively reduced oxidative phosphorylation in NSCLC. Here, we showed that targeting oxidative phosphorylation with gossypol and phenformin abrogated irinotecan resistance in NSCLC. Furthermore, irinotecan treatment by blocking oxidative phosphorylation induced synergistic anti-cancer effect in NSCLC. The pre-clinical xenograft model of human NSCLC also demonstrated a therapeutic response to the dual targeting treatment. Therefore, this combination of gossypol and phenformin increases irinotecan sensitivity as well as preventing irinotecan resistance.